Major microbial points (MMP) in halobacterial contamination of fish curing environments of Andhra coast, India - Prasad, M M; Gopakumar, K; Seenayya, G (Indian Journal of Fisheries, 2011)
The levels of microbial contamination from different environmental sources in the process of fish curing in five coastal districts of Andhra Pradesh are reported. The descending order of halophilic bacterial contamination is (1) solar salt, drying ground (DG), soil, raised cemented platform (RCP), sea sand (SS) and fish skin surface (FSS) for red halophilic bacteria; (2) DG, soil, FSS, RCP, solar salt and SS for Halomonas spp. and (3) soil, FSS, solar salt, RCP, DG and SS with respect to slime producing bacteria. A positive correlation was observed with solar salt and SS for red halophiles, soil for Halomonas spp., and DG and solar salt for slime producing bacteria. The sources of contamination in relation to cured product showed that (a) solar salt, RCP and soil for red halophilic bacteria, (b) soil, solar salt and RCP for Halomonas spp., and (c) DG, soil and solar salt for slime producing bacteria as best sets. An inverse relationship was observed in the occurrence of red halophiles and slime producing bacteria at different fish curing environs. Occurrence of Halomonas spp., in fish drying grounds is reported for the first time